(untitled) (Research, Society and Development, 2021)
Microbiology is the field of sciences that studies the morphology of microorganisms and their relationship with the environment, which is positive and / or negative. Knowledge about microbiology allows the student to understand the importance and influence of these organisms in their life, and may reflect in the reduction of diseases caused by these from health promotion, but the teaching of microbiology is restricted to traditional methodologies that do not allow students to see the same and their relationship with everyday life. With the aim of sensitizing the students about the characteristics of the microorganisms and evaluating their knowledge. This work was carried out from an extensionist action that consisted in the elaboration of workshops that offered several methodologies: Datashow, theaters, comics, written activities and practical classes,for the better understanding of microbiology by Elementary School students from two schools, one of Elementary School I and the other of Elementary School II in the municipality of Itapuranga-GO, comprising students between 8 and 15 years of age from the 5th to the 9th grade. During the workshops, diversified methodologies were used, which integrated scientific knowledge with everyday events, which instigated the interaction between student and teacher, with questions asked. The activities demonstrate that the students bring a prior knowledge about microorganisms, however superficial in relation to morphophysiology and deeper transmitted diseases.